Business Strategy, Compensation Policy and Innovation Performance: A Behavioral Perspective. (September 2017) - Chen, Liqiang; Wang, Jing
This article applies new insights into business strategies and compensation to examine why organizations adopt pay polices based on the performance of the entire organization (i.e., organization-level incentives such as profit sharing and gain sharing). Results based on a longitudinal national sample of 1, 974 Canadian workplaces show that organizations with product leadership business strategies are more likely to adopt organization-level incentives, which in turn have a positive impact on innovation performance. Implications of the findings for theory, future research and management practice are also discussed.